The Role of Islam in Shaping the Millennial Generation’s Morals and Character - Fani Putri Amaliya; Saufitri Komalasari; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Islamic education is an educational system that covers all aspects of life needed by the servants of Allah. Islamic education does not adhere to a closed system but is open to the demands of the welfare of mankind, both demands in the fields of science and technology as well as demands for fulfilling the needs of spiritual life. In entering the area of ​​practical thinking, Islamic education focuses more on problems and educational processes that must be implemented in systems, patterns, and programs with various appropriate methods to achieve goals. The strategic target of Islamic education is to instill and develop religious values ​​and scientific values ​​deeply and widely in the personality of teenagers in this millennial era so that an attitude of faith and piety will be formed in them with the ability to develop knowledge in everyday life. In other terms, the goal of Islamic education is to integrate faith and piety with knowledge in the human person to realize the welfare of life in this world and happiness in the hereafter. Islamic education cannot be understood to be limited to